DOI: 10.2298/bg20120409djordjevic
|View full text |Cite
|
Sign up to set email alerts
|

Production, nutritional and anti-oxidative properties of currant cultivars (Ribes cv.)

Abstract: Код садржаја укупних фенола вредности су биле 2,1 пута веће него у плодовима сорти црвене и беле рибизле, и кретале су се од 137,6 mg GAE/100 g код сорте Бона до 278,9 mg GAE/100 g код сорте Омета. У плодовима сорти црне рибизле садржај укупних антоцијана био је 5,6 пута већи у односу на сорте црвене рибизле, а најзаступљенији агликон антоцијана је био делфинидин, док у плодовима сорти црвене рибизле, цијанидин. У соковима произведеним од плодова испитиваних сорти регистрован је пад садржаја укупних фенола од … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 53 publications
(138 reference statements)
1
1
1
Order By: Relevance
“…Black currant fruits are larger (average weight 0.8-2 g) compared to red and white currant fruits (average weight 0.4-1 g). According to the average weight, black currant cultivar ' Čačanska Crna' (Table 2) belongs to the group of cultivars with small fruits (fruit weight up to 1 g) [28]. Similar data were reported by Stanisavljević et al [29], Ðor dević et al [28], and Milivojević et al [11], which was also confirmed in our study, where the average weight of black currant cultivar ' Čačanska Crna' was 1.05 g.…”
Section: Productivity and Basic Fruit Quality Parameterssupporting
confidence: 90%
See 2 more Smart Citations
“…Black currant fruits are larger (average weight 0.8-2 g) compared to red and white currant fruits (average weight 0.4-1 g). According to the average weight, black currant cultivar ' Čačanska Crna' (Table 2) belongs to the group of cultivars with small fruits (fruit weight up to 1 g) [28]. Similar data were reported by Stanisavljević et al [29], Ðor dević et al [28], and Milivojević et al [11], which was also confirmed in our study, where the average weight of black currant cultivar ' Čačanska Crna' was 1.05 g.…”
Section: Productivity and Basic Fruit Quality Parameterssupporting
confidence: 90%
“…The TSS is closely associated with fruit sweetness, and consumers tend to select fruits that taste sweeter. In our study, the average TSS of black currant ' Čačanska Crna' was 15.23 • Bx, which was higher than the data reported for this cultivar before [2,28,29], while blackberry ' Čačanska Bestrna' measured 9.40 • Bx, which was in agreement with a previous study [30]. Also, it is important to note that ' Čačanska Bestrna' showed a higher value of TSS compared to its parental cultivars ('Dirksen Thornless' and 'Black Satin') [25].…”
Section: Productivity and Basic Fruit Quality Parameterscontrasting
confidence: 77%
See 1 more Smart Citation